Ответы и объяснения

2011-02-03T20:26:21+03:00

5cos^2(X)-3sin^2(X)-sin(2X)=2(cos^2(X)+sin^2(X))                                               5cos^2(X)-3sin^2(X)-sin(2X)-2cos^2(X)-sin^2(X)=0                                                                  3cos^2(X)-5sin^2(X)-2sin(X)cos(X)=0   делим обе часть уравнения на cos^2(X)    3-5tg^2(X)-2tg(X)=0  назначим tg(X)=у                                                              -5у^2-2у+3=0   решаем квадратное уравнение    у1=-1 у2=3/5 . вернемся к tg(X)=y   tg(X)=-1  x1=-пи/4+(пи)к      tg(X)=3/5   х2=arctg(3/5)+(пи)к